Effect of trehalose on the preservation of freeze-dried mice spermatozoa at room temperature - Daiyu ITO; Sayaka WAKAYAMA; Yuko KAMADA; Ikue SHIBASAKI; Satoshi KAMIMURA; Masatoshi OOGA; Teruhiko WAKAYAMA (The Society for Reproduction and Development, 2019)
Freeze-drying of spermatozoa is a convenient and safe method to preserve mammalian genetic material without the use of liquid nitrogen or a deep freezer. However, freeze-dried spermatozoa (FD sperm) are not frequently used because of the low success rate of offspring after intracytoplasmic spermatozoa injection (ICSI). In this study, we determined the optimal concentration and a point of action of trehalose as a protectant for the preservation of FD sperm from different mouse strains at room temperature (RT). Although trehalose demonstrated no potential to protect the FD sperm of ICR mice against the freeze-drying procedure itself, the blastocyst rate was significantly improved when FD sperm was preserved for more than 1 month at RT (56-63% vs. 29% without trehalose). The optimal concentration of trehalose was 0.5 M. Importantly, remarkable results were obtained when spermatozoa of inbred mouse strains (C57BL/6N, C3H/He, and 129/Sv) were used, and many offspring were obtained when FD sperm that was preserved for 3 months at RT (26-28% vs. 6-11% of without trehalose) was used. However, when DNA damage in FD sperm was examined by gamma-H2Ax assays, it was found that trehalose failed to protect the FD sperm from DNA damage. These results suggest that trehalose has the potential to protect other sperm factors rather than sperm DNA during preservation at RT for longer periods and trehalose is more effective for inbred mouse strains.